2004
DOI: 10.3928/1542-8877-20040301-14
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Corynebacterium Endophthalmitis Following Laser Posterior Capsulotomy

Abstract: Abstract. Four months following uncomplicated cataract extraction, a patient underwent Nd: YAG laser posterior capsulotomy. Three days later, she presented with pain, hand motions vision, and severe anterior uveitis and vitritis. A coincident retinal detachment led to a delay in diagnosing the etiology of this intraocular inflammation. After recurrent episodes of inflammation that were initially responsive to corticosteroids, the patient underwent a vitrectomy, lens explantation, capsulectomy, and intravitreal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Recently, however, several investigators [17][18][19] reported that Corynebacterium caused endophthalmitis postoperatively. In the current study, approximately 20% of Corynebacterium strains (6/29, 20.7%) were resistant to all fluoroquinolones studied.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, however, several investigators [17][18][19] reported that Corynebacterium caused endophthalmitis postoperatively. In the current study, approximately 20% of Corynebacterium strains (6/29, 20.7%) were resistant to all fluoroquinolones studied.…”
Section: Discussionmentioning
confidence: 97%
“…Corynebacterium has been previously described to be associated with endophthalmitis after YAG capsulotomy and has been demonstrated to stay sequestered within the capsular bag and even form a capsular hypopyon. 31, 32, 35 None of the patients in the current series required intraocular lens removal or capsulectomy, which is commonly required when treating endophthalmitis caused by Propionbacterium acnes , the most common cause of delayed-onset endophthalmitis. 46 Although persistently positive vitreous cultures in endophthalmitis caused by Corynebacterium species have been reported, there were no cases of persistently positive vitreous cultures in the current series.…”
Section: Discussionmentioning
confidence: 92%
“…It is thought that the capsulotomy liberates sequestered bacteria and mobilizes their spread into the vitreous cavity. Endophthalmitis following Nd:YAG capsulotomy is not unique to C. acnes , and has been described for other bacteria, including Staphylococcus epidermidis [ 28 ] and Corynebacterium species [ 29 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%